Development And Analyzation Of Linear Positioning Table For Drilling Machine - Ab Wahab, Norfariza; Mohd Azmi, Siti Haidar Atiah; Nordin, Abd Khahar; Abdul Hadi, Dayanasari; Johari, Siti Halma; Mohd Najib, Suhaila (Asian Research Publishing Network, 2019)
Drilling is a continuous machining process. Drilling is a cutting process that uses a drill bit to cut a hole of circular cross-section in solid materials. This forces the cutting edge against the work piece, cutting off chips (swarf) from the hole as it is drilled. Various cutting tools are available for drilling, but the most common is the twist drill. Wide varieties of drill processes are available to serve different purposes such as drilling, reaming, boring, counter boring, counter sinking, spot facing, trepanning and under cutting. The objective of this project is to optimize and analyze the linear positioning table for drilling machine to make it more effective and perfect to function. Furthermore, the methods that can be used are by installing the screw on the based part of the linear positioning table for drilling machine. For this linear positioning table easy to use, the scale reading will be design on it so that operator will easily mark the desired measurement to be drill. A simple and safe design is proposed to optimize and analyze this project which is expected to function efficiently. In conclusion, this linear positioning table will be able to ease the operator work which the operator only needs to clamp once for the entire drilling process.